Analisis Yuridis Pemenuhan Hak dan Kewajiban Peserta Pemagangan berdasarkan Peraturan Menteri Tenaga Kerja Nomor 6 Tahun 2020 Tentang Penyelenggaran Pemagangan di Dalam Negeri - Aep Risnandar; Sugeng Prayitno (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Humans need an activity that can produce many activities that can be carried out by humans, one of which is through work. In the current era, getting a job is not an easy thing, where a prospective worker must have the ability and experience. One of the efforts to get a job is through an apprenticeship program, this is needed to develop work competence, productivity, discipline, attitude, and work ethics at the level of skills and expertise in accordance with the level and qualifications of the position or job. Apprenticeship training is carried out by taking into account the needs of the labor market and the business world, both inside and outside the employment relationship. Apprenticeship training is held based on a training program that refers to work competency standards, and is carried out in stages.The implementation of the apprenticeship must be initiated and based on a written agreement between the apprentice participant and the apprentice organizing company which is recognized and approved by the local District/City Office. Law in society is a means to uphold order so that the interests of society can be maintained in their relations. Laws regarding the protection of human interests are guaranteed through norms or rules. Law, as a general rule and normative rule. In the labor law it has been emphasized that apprenticeship must be made based on a written agreement between apprentice participants and employers, wherein the agreement stipulates the rights and obligations as well as the period of apprenticeship, this is done to protect the rights of apprentice participants. The position of apprentices must be legally protected so that apprenticeship activities can run smoothly according to the functions and objectives of the apprentice itself and to minimize arbitrarines